The use of folk songs in the beginning orchestra ensemble: creating context for greater connections - VanderWoude, Laura J. (Kansas State University, 2022)
The lessons included in this report focus on the use of folk songs in the beginning strings ensemble. In the first lesson, the general concept of a folk song was introduced, and students were given the opportunity to select solo literature. As the lessons progressed, students were involved in unison playing of folk songs, developing aural skills, engaging in call and response activities and analyzing multi-part literature based on common folk songs. The unit concluded with a final research-based project in which students chose a folk song to research and present to an audience. I designed these lessons with the intention to attempt more aural-based exercises with my students, as well as to include more multi-cultural music in my programming. Throughout my time in the Graduate program at Kansas State University, I have been involved in many discussions concerning the role of multicultural music in the school ensemble. In studying the music philosophies of Kodály and Small specifically, I began to consider the rich tradition of folk songs and aural-based learning included in elementary music classrooms. However, this tradition and practice does not always translate to the secondary level in traditional pedagogy. I have always held a very constructivist-based approach to music teaching. I have seen my role as a teacher to provide the knowledge, skills, resources and model for students to use and apply to future music-making. Although this is a tenant of my teaching philosophy, this final report challenged me to design activities in which students would have the opportunity to engage in student choice and self-directed learning. I believe that the strategic use of guided practice and “productive struggle” allowed for greater understanding and solidification of concepts and skills. I also began to incorporate more peer modeling and peer feedback. I began to realize that the “More Knowledgeable Other” as presented by Vygotsky did not always need to be myself, and that students could learn collaboratively and from their own trial and error. Ultimately, I used this unit based on folk songs to test my personal philosophies and to see how students would react to time spent studying folk songs more in depth. I found that lecture-based lessons and research activities did not seem to motivate students. However, activity-based lessons and student-led exploration led to greater motivation and deeper connections to both the repertoire itself and to the act of music-making.
Keywords: Music education; Orchestra; Strings; Folk songs; Multicultural